2004
DOI: 10.1038/sj.cgt.7700759
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms regulating the tumor-targeting potential of splice-activated gene expression

Abstract: Previous studies have suggested that differences in the ability of normal and malignant cells to process certain alternatively spliced pre-mRNA transcripts can be exploited as a potentially powerful means of targeting the expression of therapeutic genes to tumor cells in vivo and in vitro. Specifically, it was shown that efficient processing of minigene constructs containing the alternatively spliced CD44 exons v9 and v10 only occurs in tumor cells that express CD44 isoforms that incorporate these exons (e.g. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
9
0
2
Order By: Relevance
“…CD44 has ten alternative exons encoding its cell surface region and several recent studies have further elucidated the mechanisms leading to their observed combinations in cancer. (94,95) As the variable exons are all in the extracellular region of CD44, they are potential therapeutic targets (96,97) (Fig. 3).…”
Section: Resistance To Apoptosismentioning
confidence: 99%
“…CD44 has ten alternative exons encoding its cell surface region and several recent studies have further elucidated the mechanisms leading to their observed combinations in cancer. (94,95) As the variable exons are all in the extracellular region of CD44, they are potential therapeutic targets (96,97) (Fig. 3).…”
Section: Resistance To Apoptosismentioning
confidence: 99%
“…24 Further CASE examples include the gene CD44, which is a known marker of malignancy and invasiveness and has about ten ASEs that can occur in different combinations in its region coding for the extra-cellular portion of the protein. 20,21,23 In spite of the efforts of other groups, 25-27 a simple and efficient nomenclature to take into account all the variability generated by alternative splicing, especially for CASEs, is still missing. Here, we present a web portal, SPLOOCE, which uses a method based on regular expressions with an associated syntax.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, some ASEs and CASEs occurring in oncogenes and tumor suppressor genes have already been associated to cancer. 6,[20][21][22][23] For example, the gene NTRK1 (nerve growth factor) has a sequence variant, TrkAIII, which is common in certain tumors and lacks three exons that affect a regulatory immunoglobulinlike domain. 24 Further CASE examples include the gene CD44, which is a known marker of malignancy and invasiveness and has about ten ASEs that can occur in different combinations in its region coding for the extra-cellular portion of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…19 As a consequence, a number of interventions that either alter or exploit alternative splicing are currently under active investigation for cancer therapy. 27,28 These strategies include targeting of the fibronectin extra domain B 29 and antibody therapy against CD44v6. 30 In summary, we report here that human TF is expressed in the form of 6 distinct transcripts including wild-type TF, TF-A, TF-B, asTF, asTF-A and asTF-B (Fig.…”
mentioning
confidence: 99%